2017
DOI: 10.1093/neuonc/now294
|View full text |Cite
|
Sign up to set email alerts
|

Clinical targeted exome-based sequencing in combination with genome-wide copy number profiling: precision medicine analysis of 203 pediatric brain tumors

Abstract: The combination of OncoPanel and OncoCopy multiplex genomic assays can identify critical diagnostic, prognostic, and treatment-relevant alterations and represents an effective precision medicine approach for clinical evaluation of pediatric brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 42 publications
1
64
1
4
Order By: Relevance
“…13). Similar efforts on childhood cancers such as pediatric glioma and neuroblastoma were also reported (14,15). These studies laid the foundation for the approval of clinical use of highthroughput sequencing-based gene panels such as the Foundation Medicine panel and Memorial Sloan Kettering IMPACT panel by the FDA.…”
Section: Introductionmentioning
confidence: 72%
“…13). Similar efforts on childhood cancers such as pediatric glioma and neuroblastoma were also reported (14,15). These studies laid the foundation for the approval of clinical use of highthroughput sequencing-based gene panels such as the Foundation Medicine panel and Memorial Sloan Kettering IMPACT panel by the FDA.…”
Section: Introductionmentioning
confidence: 72%
“…Several recent publications have defined the utility of broad genomic screening in pediatric CNS tumors, including the following: (a) University of California San Francisco, using targeted sequencing of 510 genes; (b) Dana‐Farber Cancer Institute, using the OncoPanel of 309 genes, OncoCopy, and array comparative genomic hybridization; (c) University of Washington, utilizing the OncoPlex platform evaluating 262 cancer‐related genes; (d) University of Michigan, utilizing transcriptome sequencing augmented by either whole exome sequencing or targeted sequencing of 1706 genes; and (e) a study conducted at Foundation Medicine, Inc. reporting the analysis of 315 cancer‐related genes in 282 pediatric LGGs and HGGs . We report the utility of fusion analysis of pediatric CNS tumors using a smaller RNA‐based panel consisting of 53 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Many tertiary care centers currently utilize a broad, panel‐based approach for assessment of potentially actionable genetic alterations in CNS tumors. Recently, a handful of studies demonstrated the feasibility and utility of incorporating molecular diagnosis into the care of children with CNS tumors . These reports detail the use of large 300‐500‐gene panels focused on mutations common in human cancers but not specific to pediatric tumors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, altered QKI expression was implicated in various human cancers, including colorectal cancer, 33 paediatric brain tumours, 34 glioma, 35 renal clear cell carcinoma, 9 lung cancer 17 and prostate cancer. 18 In this study, we measured QKI-6 expression and determined its role in regulating bladder cancer in vitro and in vivo, and we also investigated the molecular mechanism underlying QKI-6's effect in bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%